SHARIA ECONOMY AS A SYSTEMIC SOLUTION TO ERADICATING CORRUPTION: BUILDING TRANSPARENCY AND ACCOUNTABILITY BASED ON ISLAMIC VALUES - Arifa Pratami; Dina Aghnia; Elvina Sari; Putri Afriza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
Corruption is a systemic problem that undermines economic development, erodes public trust, and distorts resource allocation. Although various efforts have been made to address it, corruption remains entrenched in many countries due to the lack of a moral and institutional framework that ensures transparency and accountability. This paper explores Islamic economics as a systemic and value-based solution to eradicate corruption. Rooted in Islamic principles such as trust (amanah), justice (‘adl), accountability (hisbah), and public welfare (maslahah), the Sharia economic system not only regulates transactions but also promotes integrity and spiritual awareness. Using qualitative methods supported by descriptive analysis, this research outlines how Islamic financial governance, zakat institutions, Sharia-compliant public audits, and ethical leadership models offer practical mechanisms to reduce corruption. This paper also discusses historical Islamic governance practices that demonstrate successful anti-corruption models and provides recommendations for the adaptation of contemporary policies. The findings indicate that the Sharia economy has the potential to promote a culture of accountability and integrity, making it a viable alternative in combating corruption in Muslim-majority countries and beyond.